Longitudinal Analysis of the Effect of Repeated Transarterial Chemoembolization for Liver Cancer on Portal Venous Pressure - Constantine Frangakis (Frontiers Media S.A., 2021)
ObjectivesInvestigate long-term effects of repeated transarterial chemoembolization (TACE) on portal venous pressure (PVP) using non-invasive surrogate markers of portal hypertension.MethodsRetrospective, Institutional Review Board-approved study. 99 patients [hepatocellular carcinoma (HCC) group (n=57); liver metastasis group (n=42)] who underwent 279TACEs and had longitudinal pre-/post-therapy contrast-enhanced-MRI (n=388) and complete blood work were included. Outcomes of interest were platelet count (PC), spleen volume, ascites and portosystemic collaterals. Variables included TACE type/number, tumor type, microcatheter location, Child-Pugh, baseline tumor burden (tumor number/total/largest size), vessel invasion, alpha-fetoprotein, Eastern Cooperative Oncology Group (ECOG) performance status, and Model for End-Stage Liver Disease (MELD) score. Generalized Estimating Equations assessed the associations between TACE and outcomes. Power analysis determined the sample size was sufficient.ResultsNo significant change in PC over time was observed in either groups, regardless of liver function (P>0.05). Baseline spleen volume was 226 cm3 for metastatic group, and was larger by 204 cm3 for HCC group (P<0.001). Spleen volume increased by 20 cm3 (95%CI: 8-32; P=0.001) for both groups after 1stTACE and by 16cm3/TACE (P=0.099) over the full follow-up (up to 9TACEs). Spleen volume also tended to increase by 23cm3 (95%CI: -1–48; P=0.064) with higher tumor burden. Odds of developing moderate/severe ascites for metastatic patients was decreased by 0.5 (95%CI: 0.3–0.9; P=0.014), regardless of the Child-Pugh, and increased by 1.5 (95%CI: 1.2–1.9; P<0.001) among HCC patients with unstable Child-Pugh, whereas no change was noted with stable Child-Pugh. HCC patients with unstable Child-Pugh demonstrated a significant increase in portosystemic collaterals number over time (P=0.008). PVP-related complications such as variceal bleeding post-TACE were low (0.4%).ConclusionRepeated TACEs did seem to have an impact on PVP. However, the increase in PVP had marginal effects with low portal hypertension-related complications.